Dynamic Price Competition, Learning-by-Doing, and Strategic Buyers - Sweeting, Andrew; Jia, Dun; Hui, Shen; Yao, Xinlu (American Economic Review, 2022)
We examine how strategic buyer behavior affects equilibrium outcomes in a model of dynamic price competition where sellers benefit from learning-by-doing by allowing each buyer to expect to capture a share of future buyer surplus. Many equilibria that exist when buyers consider only their immediate payoffs are eliminated when buyers expect to capture even a modest share of future surplus, and the equilibria that survive are those where long-run market competition is more likely to be preserved. Our results are relevant for antitrust policy and our approach may be useful for future analyses of dynamic competition. (JEL C73, D21, D43, D83, K21, L13, L40)